Characteristic submucosal alteration in biliary carcinogenesis of pancreaticobiliary maljunction with a focus on inflammasome activation. (1st November 2022) - Yamashita, Shoko; Takasu, Chie; Morine, Yuji; Ishibashi, Hiroki; Ikemoto, Tetsuya; Mori, Hiroki; Yamada, Shinichiro; Oya, Takeshi; Tsuneyama, Koichi; Shimada, Mitsuo
Abstract: Background: This study investigated submucosal alterations in biliary carcinogenesis of pancreaticobiliary maljunction (PBM). Methods: Thirty‐three patients with PBM (including seven with gallbladder [GB] cancer), four with neither biliary tract cancer nor PBM who underwent pancreaticoduodenectomy (controls), and seven with chronic cholecystitis without PBM were enrolled. Protein expression of α‐smooth muscle actin (αSMA), CD68, and CD204 in the GB lamina propria and that of NLRP3 and caspase 1 in the GB epithelium and lamina propria were examined. Results: Compared with the control and cholecystitis groups, αSMA expression was higher in the cancerous part (stroma) of the GB in patients with GB cancer + PBM and in the lamina propria of patients with PBM. The CD204/CD68 ratio in the lamina propria was higher in the PBM group than in the control and cholecystitis groups. NLRP3 and caspase 1 expression in both the lamina propria and epithelium was higher in the PBM than control group. In the PBM group, NLRP3‐ and caspase 1‐positive cells in the lamina propria were located near the epithelium. Conclusion: Activated fibroblasts and M2 macrophages in the GB lamina propria may be associated with biliary carcinogenesis of PBM, possibly through inflammasome activation. Abstract : Yamashita and colleagues present their findings on characteristic submucosal changes in biliary carcinogenesis in patients with pancreaticobiliary maljunction. They propose that activated fibroblasts and M2 macrophages in the lamina propria of the gallbladder may be associated with biliary carcinogenesis in patients with pancreaticobiliary maljunction, possibly through NLRP3 inflammasome activation.